Formation of simultaneous denitrification and methanogenesis granules in biological wastewater treatment. (July 2017) - Kodera, Toshimitsu; Akizuki, Shinichi; Toda, Tatsuki
Graphical abstract: Highlights: SDM granule was successfully formed for the first time from dispersed sludges. SDM granule formation was only dependent upon an increased substrate concentration. Nitrate increased EPS production and subsequently enhanced SDM granule formation. The formed SDM granule achieved COD and nitrate removal efficiencies of above 90%. Abstract: In this study, simultaneous denitrification and methanogenesis (SDM) granules were formed for the first time from dispersed digested and denitrifying sludges. The successful formation of the SDM granules occurred through an increase in substrate concentration of wastewater. Comparatively, formation of conventional methanogenic granules requires an increase in upflow velocity as well as substrate concentration. Nitrate, which is known to inhibit methanogenesis, was key in increasing extracellular polymeric substances (EPS) production because of the protection mechanism of methanogens. The produced EPS clearly enhanced the formation of the SDM granules. The formed SDM granules showed high simultaneous removal efficiencies above 90% for the chemical oxygen demand (COD) and nitrate under high organic and nitrate loading rates (10 g-COD L −1  d −1 and 0.67 g-NO3 − -N L −1  d −1, respectively). Although the methane concentration in biogas from the SDM granules were relatively low (60%) compare to the conventional methanogenic granules, it remains feasible for energy recovery.